Experience of Using Domestic High-Frequency Electric Welding Technology in Surgical Treatment of Patients with Abdominal Pathology - A.M. Babiy; B.F. Shevchenko; V.M. Ratchik; D.D. Kunkin (Gastroenterologìa, 2014)
The article presents the experience of using electric welding technology of biological tissues with domestic high-frequency electrical generator EC 300 M1 in 176 patients at open and laparoscopic surgery for abdominal pathology. The analysis of findings showed that electric welding of living tissue provides reliable hemostasis, promotes tissue repair after their separation.